Penyusunan Sistem Evaluasi Kinerja Layanan Dalam Membangun Tata Kelola TI Berbasis Komputasi Awan - N. Tri Suswanto Saptadi; Hans Christian Marwi (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2016)
Engineering models design on performance application is expected to contribute to the development of IT governance system in the hospital. Engineering models are developed using a framework standard. As public facility in the area of health, hospital management requires performance services application to identify the needs of stakeholders. Services performance application design require a good step in the preparation thus it takes study of relevant theory. The methods in the study of the theory is the TOGAF ADM approach. The presence of cloud computing technology can support operational activities at the hospital. The challenge is how hospitals can adopt the technology. An effective strategy derived from the results of the services performance evaluation therefore the use of technology can create effective and efficient IT governance from financial positions. The method used in compiling the IT governance strategy is the system architecture which includes interface design, infrastructure management, classification, definition, and connectivity design. The main components include business architecture, information (data), applications, and technologies. The result of engineering models design have shown that hospitals can use it as a standard architecture model based on a structured system with support from cloud computing technology.